Genetic evidence for a product of the Fv-1 locus that transfers resistance to mouse leukemia viruses. - Tennant, R W (1976)
Extracts of mouse cells have been shown to transfer to N- or B-trophic host range types of mouse leukemia viruses. The genetic specificity of the inhibition was tested in two ways: (i) by correlating the Fv-1 genotype of a number of mouse strains with the restriction-transferring activity of extracts of the respective embryo cell cultures, and (ii) by correlating the Fv-1 genotype of BLC3F2 (C57BL/6 female [Fv-1bb] by C3H male [Fv-1nn] parental strains) mouse embryos, which segregate the Fv-1 alleles in a 12:1 ratio, with the inhibitor activity of extracts of the cells from each embryo. Five independent matings, totaling 45 individual embryos, were tested. Each embryo was cultured, and the Fv-1 genotype was determined independently by titration of N- and B-tropic viruses; the extracts of replicate secondary cultures were tested for their effect on infection of permissive cells by N- and B-tropic viruses. The specific-restriction-transferring activity of the embryos was found to segregate with the appropriate Fv-1 genotype. These res-lts confirm the suggestion that the inhibitor of the leukemia virus host range types in the cellular extracts is a product of the Fv-1 locus.